Case Report: Primary and Acquired Resistance Mechanisms of Nimotuzumab in Advanced Esophageal Squamous Cell Carcinoma Revealed by Targeted Sequencing - Sun, Dantong; Yan, Weihua; Zhu, Hua; Liu, Qiaoling; Hou, Helei (Frontiers in Oncology, 2020)
Esophageal squamous cell carcinoma (ESCC) is a deadly disease with a low 5-year survival rate. Anti-epidermal growth factor receptor (EGFR) therapy has been widely used in the treatment of malignancies, and chemotherapy regimens that include nimotuzumab have been confirmed to have satisfactory efficacy among esophageal carcinoma (EC) patients. However, a subpopulation of patients may develop resistance to nimotuzumab. Here, we report an advanced ESCC patient who experienced hyperprogressive disease induced by immune checkpoint inhibitors and was then treated with a chemotherapy regimen containing nimotuzumab. NGS examination of this patient demonstrated that PIK3CA mutation and a RICTOR amplification might participate in primary and acquired resistance to nimotuzumab, respectively, via the PI3K/AKT/mTOR signaling pathway.